PENGARUH PARTISIPASI ANGGARAN TERHADAP KESENJANGAN ANGGARAN DENGAN INFORMASI ASIMETRI DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL MODERATING (Studi Empiris Pada SKPD Kota Pekanbaru) - Topan Surya Perdana; Taufeni Taufik; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to test: 1) The effect of budgetary participation in the budgetary slack. 2) Effect of budgetary participation in budgetary slack with information asymetry as moderating variables. 3) Effect of budgetary participation in budgetary slack with environmental uncertainty as moderating variables. The populations of this research are chief financial subsections, chief progamme subsections and financial staff that work on the SKPD in Pekanbaru city. The sampling technique using purpose sampling. Total repondents in this research are 75 respondents. The data of this research uses primary data is distributing questionnaire directly and analyzed using SPSS 20. The method of analysis are using Moderated Regression Analysis (MRA). The results of this study indicate that 1) Budgetary participation has effect toward budgetary slack 2) Information asymetry has effect on the relationship between budgetary participation on budgetary slack 3) Environmental uncertainty has effect on the relationship between budgetary participation on budgetary slack.Keywords: Budgetary slack, budgetary participation, information asymmetry, and environmental uncertainty